Novel theories and applications of global information resource management - Zhang, Zuopeng (Justin), 1973- (Advances in library and information science (ALIS) book series., 2020)
""This book examines developing practices for businesses to effectively manage their assets on a global scale. It also examines the implementation of technological innovation into business techniques as well as the methods of controlling information in a contemporary society"--Provided by publisher"--